Comparative analysis of the optic nerve microvasculature between different optic disc phenotypes of normal-tension glaucoma patients - Min Kyung Song; Yunhan Lee; Joong Won Shin; Jin Yeong Lee; Ji Wook Hong; Michael S. Kook (BMC Ophthalmology)
Abstract Purpose To determine whether the optic nerve head (ONH) and parapapillary choroidal vessel density (VD), measured by optical coherence tomography angiography (OCTA), differ between two common optic disc phenotypes (ODPs) in normal-tension glaucoma (NTG). Design A retrospective case-control study. Methods This cross-sectional study analyzed 100 NTG patients with visual field (VF) loss confined to a single hemifield (50 eyes with focal ischemic [FI] ODP and 50 eyes with myopic glaucomatous [MG] ODP, matched for age [≤ 10 years] and VF severity [mean deviation ≤ 1 dB]) as well as 50 healthy eyes. Using OCTA, ONH VD (ONH-VD) was evaluated on a 4.5 × 4.5 mm ONH en-face image using the whole-signal mode. The parapapillary choroidal VD (pCVD) was measured on en-face choroidal layer image within the entire β-parapapillary atrophy (β-PPA) zone using imageJ software. The ONH-VD and pCVD were compared among the three groups. The relationships between ONH-VD and pCVD outcomes and various clinical variables were assessed using linear regression analyses. Results The average ONH-VD and pCVD were significantly lower in eyes with MG ODPs than those with FI ODPs (56.9% vs. 60.4%, 67.1% vs. 71.8%; both P < 0.05). Multivariable linear regression analysis indicated that MG ODP, lower peripapillary retinal nerve fiber layer thickness and VD in the hemiretina, corresponding to hemifield VF loss, in addition to the presence of choroidal microvasculature dropout, were significantly associated with lower ONH-VD and pCVD (P < 0.05). Conclusions The OCTA-measured ONH-VD and pCVD are significantly lower in eyes with MG ODPs rather than FI ODPs. MG ODP is independently associated with lower ONH-VD and pCVD in NTG eyes.